Editorial: Engaging with Turbulence. Issue 1 (1st March 2022) - Andersen, Tawny; Bhagwati, Sandeep; Carrasco, Victoria; Davida, Dena; Scales, Barbara; Sheriff, Yves
Abstract : The call for papers for this inaugural issue of TURBA opened with two truisms: "Live arts have existed long before history. At all times, and in all cultures around the world, people have performed for others." Yet we have just lived through more than a year during which the second of these assertions was falsified almost everywhere on the planet. When performing for and near others was not only, as it often is, precarious or subversive, but outright life-threatening. Was it wise or necessary, at such a historic juncture, to embark on a new journal that focuses on how cultural communities around the world foster and debate live performances? We obviously believe so.